PENGARUH DONGENG DIGITAL TERHADAP PERKEMBANGAN BAHASA RESEPTIF ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL TEMBESI - Winarti, Sri; Indryani; Akhmad Fikri Rosyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low receptive language ability of children aged 5–6 years at TK Aisyiyah Bustanul Athfal Tembesi. The method used was quantitative research with a quasi-experimental design employing a non- equivalent control group pretest-posttest design. The sample consisted of two groups, namely the experimental group and the control group. Data collection was carried out through observation. The results showed a significant improvement in the receptive language ability of children in the experimental group after being given treatment in the form of digital storytelling, with the average score increasing from 13.66 to 27.71, while the control group showed only a slight increase from 12.88 to 13.77. The results of hypothesis testing using a t-test showed a significance value of 0.000 < 0.05, indicating that there is a significant effect of digital storytelling on the development of receptive language in children aged 5–6 years.